Fuzzy Semimaximal ideals - I, M.A. Hadi; M. A. Hamil (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
Let R be a commutative ring with identity. A proper ideal I of R is called semimaximal if I is a finite intersection of maximal ideals of R. In this paper we fuzzify this concept to fuzzy ideals of R, where a fuzzy ideal A of R is called semimaximal if A is a finite intersection of fuzzy maximal ideals. Various basic properties are given. Moreover some examples are given to illustrate this concept.